A comparative study of short-term intensive and prolonged low-intensity simulation training on clinical competence among medical students - Yao Zhou; Nvwa Jin; Jinqiu Fu; Hanxiang Zhan (Frontiers in Medicine, 2026)
Introduction Clinical simulation training is widely used to improve procedural proficiency and patient safety; however, the relative effectiveness of different training schedules remains uncertain. This study compared clinical competence outcomes associated with short-term intensive and prolonged distributed simulation training among medical students. Methods This prospective, non-randomized comparative cohort study included 48 fifth-year medical students. Based on their preferences, participants selected either a 15-day intensive simulation program (Group A, n = 24; approximately 8 h/day) or a 5-month distributed simulation program (Group B, n = 24; no more than 2 h/day). The total training duration was comparable between the groups. After training, both groups participated in team-based clinical skills competitions. Outcomes included scores from the Shandong Provincial College Student Medical Technology Skills Competition and structured post-training assessments of specialized knowledge, clinical skills, teamwork, emergency response capacity, and integrated professionalism completed by instructors and students. Results Group A achieved higher competition scores than Group B in basic surgical procedures, internal medicine procedures, gynecological and pediatric procedures, emergency medical skills, and physician-patient communication skills (all p < 0.05). The between-group difference in comprehensive case-analysis skills was not statistically significant ( p = 0.065). Group A also received higher instructor ratings and reported higher self-assessment scores across all evaluated domains than Group B (all p < 0.05). Discussion Participation in short-term intensive simulation training was associated with better immediate competition performance and more favorable instructor and student ratings than participation in prolonged distributed training. However, because group allocation was preference-based and potentially important baseline variables were unavailable, the findings do not establish causal superiority or long-term benefits of intensive training. Concentrated, feedback-rich simulation may be useful when immediate technical and team performance is prioritized, but randomized studies incorporating retention and clinical-transfer outcomes are needed.